Studi Etnobotani Tumbuhan Obat di Kelurahan Pendahara Kecamatan Tewang Sangalang Garing Kabupaten Katingan - Araina, Elga; Rahmi, Ennike Gusti; Neneng, Liswara; Basuki, Bejo; Wijaya, Nuriman; Akhmadi, Akhmadi; Fahrina, Ririn; Adam, Chaidir; Panny, Priscilla; Herniati , Melly (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
The use of plants by a part of society in the cultural scope is studied in a special branch of biological science, namely ethnobotany. Ethnobotany is a science that studies the relationship between humans and plants and their environment based on the life experienced by society. This study aims to find out what types of plants are used as medicine by the local community in Pendahara Village and to discover how to process and use plants as medicine by the community. The method in this study employs an exploratory survey method, which is research that seeks to explore something new, not widely known by the public, and aims to be studied more deeply by conducting direct interviews with sources and informants, namely the community in Pendahara Village. Data collection techniques are carried out by providing interviewers, observations, interviews and documentation. The results of the study found 16 types of plants that can be used as traditional medicine. The results of the study found 16 types of plants that can be used as traditional medicine. These plant species are Orthosiphon aristatus, petindis plants, Hippobroma longifora, Tinospora cordifolia, Arcangesia flava (L.) Merr, Annona muricate, Hibiscus rosa-sinensis L., Asplenium nidus L., Averrhoa bilimbi L., Areca catechu, Psidium guajava L., Cordyline, Acorus calamus L., Phyllanthus niruri L., Kalanchoe pinnata, and Luvunga sarmentosa. It was concluded that the use of the plant as a traditional medicine has been felt to be effective in external and internal medicine.